UbiTap: Leveraging Acoustic Dispersion for Ubiquitous Touch Interface on Solid Surfaces - Kim, Hyosu; Byanjankar, Anish; Liu, Yunxin; Shu, Yuanchao; Shin, Insik (ACM Conference on Embedded Networked Sensor Systems (SenSys), 2018)
With the omnipresence of computing devices in our daily life, interests in ubiquitous computing interfaces have been growing. In response to these interests, various studies have introduced on-surface input techniques which use surrounding objects’ surface as a touch input tool. However, they are yet struggling in supporting a ubiquitous interaction due to their requirements on specific hardware or environments. In this paper, we propose UbiTap, an input method that turns any solid surface into a touch input space, by using sound (i.e., with the help of microphones already present in most commodity devices). More specifically, we develop a novel touch localization technique which leverages a physical phenomenon, called dispersion, that sound exhibits while traveling through solid surfaces so as to address challenges which limit existing acoustic-based solutions in terms of portability, accuracy, usability, robustness, and responsiveness. Our extensive experiments with the prototype of UbiTap show that it can support sub-centimeter accuracy on various surfaces with quite a small amount of user calibration efforts. In our experience with real users, UbiTap significantly improves usability and robustness, enabling more exciting applications to emerge.